Dawan Language Shift in Amanuban Society in Family Context (Universitas Negeri Semarang, 2019)
The purpose of this study are to explain form of language shift and to find out of facor that be background in Dawanese shifting in Amanuban society in South Central Timor regnancy. Data are collected by using SLC (simak libat cakap) and it is continued by using recording taking note method. Data analysis is done is some stages, there are data collection, data reduction, data resentation, and conclusion. The results is this study are Dawanese has got shifting in Amanuban society through: (a) words, (b) phrases, (c) sentences, and factors that be background in Dawanese shifting, through (a) ages, (b) mixed marriage, (c) occupation, and (d) mobility population. Based on the results above, Dawanese shifting happened in Amanuban society especially in family can be seen from form of language, there are words, phrases, and sentences. The main factor cause Dawanese shifting is education factor that rise another language.